2023
DOI: 10.21203/rs.3.rs-3171622/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolomic Profiles of Sleep-Disordered Breathing are Associated with Hypertension and Diabetes Mellitus Development: the HCHS/SOL

Abstract: Sleep-disordered breathing (SDB) is a prevalent disorder characterized by recurrent episodic upper airway obstruction. In a dataset from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL), we applied principal component analysis (PCA) on seven measures characterizing SDB-associated respiratory events. We estimated the association of the top two SDB PCs with serum levels of 617 metabolites, in both single-metabolite analysis, and a joint, penalized regression analysis using the least absolute shrin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…Both lipids and cofactors/vitamins had subpathways (e.g., ketone bodies, acyl glutamine, pantothenate and CoA metabolism, nicotinate and nicotinamide metabolism) that had high percentage of statistically significant associations with sleep timing phenotypes. SDB phenotypes had the highest percentage of statistically significant associations among lipids, especially progestin steroids, phosphatidylethanolamine, diacylglycerols, pregnenolone steroids and sphingomyelins, which is consistent with our previous research findings (43). As for the sleep duration domain, the top subpathways with the highest percentage of significant associations were bacterial/fungal, amino sugar metabolism, nicotinate and nicotinamide metabolism, primary bile acid metabolism, corticosteroids, and polyamine metabolism.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Both lipids and cofactors/vitamins had subpathways (e.g., ketone bodies, acyl glutamine, pantothenate and CoA metabolism, nicotinate and nicotinamide metabolism) that had high percentage of statistically significant associations with sleep timing phenotypes. SDB phenotypes had the highest percentage of statistically significant associations among lipids, especially progestin steroids, phosphatidylethanolamine, diacylglycerols, pregnenolone steroids and sphingomyelins, which is consistent with our previous research findings (43). As for the sleep duration domain, the top subpathways with the highest percentage of significant associations were bacterial/fungal, amino sugar metabolism, nicotinate and nicotinamide metabolism, primary bile acid metabolism, corticosteroids, and polyamine metabolism.…”
Section: Resultssupporting
confidence: 92%
“…In a recent study, glycine was found to be depleted in blood among Hispanic/Latino individuals with severe SDB, likely due to microbiome changes in an oxygen-poor environment (46). Four other metabolites – 1-oleoyl-GPE (18:1), 1-(1-enyl-palmitoyl)-GPC (P-16:0)*, pregnenolone sulfate, 5alpha-pregnan-3beta,20alpha-diol monosulfate (2), previously reported to be associated with novel SDB phenotype metrics after dimension reduction in our prior work in HCHS/SOL (43), were here also associated with several SDB phenotypes as well as with phenotypes from domains including insomnia, sleep timing, and heart rate during sleep.…”
Section: Discussionmentioning
confidence: 99%